PENERAPAN EDUCAPLAY DENGAN STRATEGI KOMPETISI KELOMPOK KECIL UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DALAM PEMBELAJARAN MATEMATIKA KELAS III SD - Nurjanah, Elvina Isna; Wulandari, Andhika Ayu; Rahayu, Christina Puji (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to improve the social skills of third-grade elementary school students through the implementation of Educaplay combined with a small-group competition strategy. The research focuses on the social-emotional competencies outlined in the CASEL framework, particularly the relationship skills domain, which includes communication, collaboration, social awareness, conflict resolution, and social engagement in learning. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, conducted at SD N Jombor 03, Bendosari District, Sukoharjo Regency. The instruments used were social skills questionnaires, observations, and documentation. The results showed an increase in the average social skills score from 56.9% in the pre-action stage to 83.6% in the second cycle. Furthermore, all students achieved scores above 75% in the second cycle, with each obtaining ?45 out of 60 points. Observations also confirmed improved social behaviors among students. Thus, the application of Educaplay with a small-group competition strategy proved to be an effective instructional approach to enhance elementary students’ social skills.